Generation Of Mode-Locked Ytterbium Doped Fiber Ring Laser Using Few-Layer Black Phosphorus As A Saturable Absorber - Hisyam, Mohamad Badrol; Mohd Rusdi, Muhammad Farid; Abdul Latiff, Anas; Harun, Sulaiman Wadi (IEEE, 2017)
We demonstrate the generation of mode-locked pulses from a double-clad ytterbium-doped fiber laser (YDFL) employing a saturable absorber (SA) made of a few layers of black phosphorus (BP). The BP SA was prepared by mechanically exfoliating BP crystal and spreading the acquired BP flakes on a piece of scotch tape. The tape was then sandwiched between two ferrules and incorporated in a YDFL cavity to achieve a stable mode-locked operation at 1085.58 nm with a repetition rate of 13.5 MHz. A maximum pulse energy of 5.93 nJ was obtained at pump power of 1322 mW with the output power of 80 mW. Our study may well be the first demonstration of the BP-based mode-locked fiber laser that should shed some new insights into two-dimensional layer materials related photonics.